2023
DOI: 10.54910/sabrao2023.55.2.18
|View full text |Cite
|
Sign up to set email alerts
|

Phenology, Crop Stand, and Dry Matter Production of Wheat in Response to Beneficial Microbes and Organic Matter Sources

et al.

Abstract: Adding organic matter to soil proved an efficient strategy for restoring soil fertility and improving crop dry matter – an indicator of yield potential. In this regard, evaluating the sources of organic matter (OM) (control, poultry manure [PM], farmyard manure [FYM], compost, and mungbean residues [MR]) to provide 120 kg N ha-1 and effective microbes (EM) (0, 100, 200, and 300 L ton-1 of OM) as 2% solution proceeded in field conditions during 2017–2019. The sowing of wheat seeds (cv. Pirsabak 2015) at 120 kg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
0
0
Order By: Relevance
“…Additionally, biochar can enhance microbial activity, providing the habitat for microbes (Palansooriya et al 2019). FYM, on the other hand, provides a direct source of organic matter to the soil (Khan et al 2023), enriching it with readily decomposable materials and nutrients that support microbial communities and organic carbon accumulation (Leuther et al 2022). The synergistic effect observed in the Biochar + FYM treatment suggests that the combination of these amendments enhances their individual contributions to carbon sequestration.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, biochar can enhance microbial activity, providing the habitat for microbes (Palansooriya et al 2019). FYM, on the other hand, provides a direct source of organic matter to the soil (Khan et al 2023), enriching it with readily decomposable materials and nutrients that support microbial communities and organic carbon accumulation (Leuther et al 2022). The synergistic effect observed in the Biochar + FYM treatment suggests that the combination of these amendments enhances their individual contributions to carbon sequestration.…”
Section: Discussionmentioning
confidence: 99%
“…The research demonstrated that for better crop growth and net return, farmers could apply organic compost to their lands for about USD 4.50 per hectare, compared with spending USD 17 per hectare on synthetic fertilizers (Oluoch-Kosura et al, 2004). Other products that promote optimal plant growth, strengthen them against environmental stressors and boost their production can also replace expensive chemical fertilizers (Zubkova et al, 2022;Khan et al, 2023;Bastaubayeva et al, 2023). For that, a natural alternative is the cytokinin-based bio-stimulant obtained from plant extracts that contain nitrogen, phosphorus, and other elements, which can easily promote the growth and development of shoots, flowers, roots, and other organs (Grzegorczyk-Karolak et al, 2021;De-Góes et al, 2021).…”
Section: Introductionmentioning
confidence: 99%